The little handbook of Windows Memory Analysis : Just some thoughts about memory, Forensics and Volatility ! - Fortuna, Andrea 1978-; Wayne, Jason ([Rome] : c, 2019)
This handbook is dedicated to a deep dive on Microsoft Windows memory, starting from a brief description of memory management, moving on to an extended reference of Volatility Framework and coming to a list of acquisition and analysis workflows.
Includes index.
Includes bibliographical references.
Keywords: Criminal investigation; Forensic sciences; Computer crimes -- Investigation; Computer security